Pengembangan Produk UMKM Budidaya Rumput Laut di Desa Panda, Kec.Palibelo, Kabupaten Bima - Irma Mardian; Lilis Putriyani; Siti Syarah A.; Ayu Wulandari; Nur Annisah; Uswatun Hasanah; Khofifah Indar P (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
This seaweed management activity as a regional specialty was carried out during the MBKM KKN-T activity for the Creative Business Business planning course in Panda Village. The aim of this service activity is to help create product innovations from local potential to help increase the income of the Panda Village community. Seaweed itself is one of the superior products of the local area which still lacks processing and knowledge of the benefits of seaweed itself. Seeing the existing opportunities, we developed seaweed such as seaweed sticks and conducted training on making attractive packaging with the aim of helping develop regional potential and increasing community creative businesses. collaborate with various parties.